Unraveling the Biosynthetic Logic Behind the Production of Ramoplanin and Related Lipodepsipeptide Antibiotics - Oleksandr Yushchuk; Kseniia Zhukrovska; Elisa Binda; Flavia Marinelli (Fermentation)
This review focuses on the genetic and biotechnological aspects of the biosynthesis of ramoplanin (Rmp), enduracidin (End), and other related lipodepsipeptide antibiotics, herein named collectively ramoplanin and ramoplanin-related lipodepsipeptide (RRLDPs). These compounds exhibit a promising antimicrobial activity against Gram-positive bacterial pathogens, showing no cross-resistance with vancomycin. Rmp is in clinical development for human treatment and End has been used as animal growth promoter for decades. Other RRLDPs as ramoplanose and janiemycin had been poorly investigated in the past, whereas new molecules as chersinamycin have been recently discovered, attracting a renewed interest in this class of antibiotics. Nowadays, sequence and annotation of the biosynthetic gene clusters (BGCs) of Rmp, End, and several other RRLDPs are available, and researchers are focused on understanding the biosynthetic logic behind the production of these compounds. Interestingly, producers of Rmp and chersinamycin belong to the so-called “non-common” actinomycetes from the family Micromonosporaceae, whereas End is produced by different members of the genus Streptomyces. To the best of our knowledge, no reviews summarize and systematize the current information on the biosynthesis of RRLDPs. Therefore, in this review, we aim to fill this gap. We first describe and compare the BGCs for known RRLDPs, giving an insight on how they were discovered and developed. Next, we review the biosynthetic pathways of these antibiotics, as well as the regulation of their biosynthesis. Then, we focus on the production processes of RRLDPs, demonstrating how cultivation and nutritional factors influence their production. Finally, we provide a short outline of future directions in studying RRLDPs.